1993
DOI: 10.1152/ajpendo.1993.264.6.e855
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases muscle GLUT-4 levels and insulin action in subjects with impaired glucose tolerance

Abstract: A decline in insulin sensitivity is associated with aging, inactivity, and obesity. The effects of exercise training on glucose homeostasis independent of weight loss in older glucose-intolerant individuals are not well established. We examined the effects of exercise training on oral glucose tolerance, insulin action, and concentration of the GLUT-4 glucose transporters in skeletal muscle. Exercise training at 50 and 75% of heart rate reserve was performed for 12 wk in 18 individuals (age = 64 +/- 2, body fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
211
3
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(233 citation statements)
references
References 2 publications
12
211
3
7
Order By: Relevance
“…We also demonstrated that after exercise training glucose uptake and clearance increased with the high-dose insulin infusion in agreement with a previous study showing an improvement in peripheral insulin sensitivity following exercise training in insulin-resistant men, who were studied 96 h after the last exercise session [34].…”
Section: Discussionsupporting
confidence: 92%
“…We also demonstrated that after exercise training glucose uptake and clearance increased with the high-dose insulin infusion in agreement with a previous study showing an improvement in peripheral insulin sensitivity following exercise training in insulin-resistant men, who were studied 96 h after the last exercise session [34].…”
Section: Discussionsupporting
confidence: 92%
“…The duration (3 months) of exercise at the frequency and intensity chosen for the current study may simply have been insufficient for the improvements that were expected. However, previous studies including our own in equally obese but older subjects with obesity and type 2 diabetes, have shown improvements in insulin sensitivity and glycaemic control with similar or even less rigorous exercise regimes [13,14]. Another question is whether it would have been preferable to combine the exercise regime with a weight-losing low-energy diet.…”
Section: Discussionmentioning
confidence: 93%
“…Similar to our study, they demonstrated marked insulin resistance and beta cell failure although these subjects had very good chronic glycaemic control. Aerobic exercise has been shown to be effective in improving insulin sensitivity in patients with obesity, prediabetes and type 2 diabetes [13,14,16]. The landmark diabetes prevention studies have proven the efficacy of exercise intervention in preventing progression from IGT to diabetes [9,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement in insulin resistance through chronic physical activity independent of weight change likely involves changes in body composition -in particular, reductions in visceral fat (14), as well as augmented expression of GLUT-4 protein in skeletal muscle (56,57), and enhanced metabolic efficiency of muscle (58,59). The lipid improvements independent of significant weight reduction may also be mediated by improvements in body composition, such as reductions in visceral fat (60), but apparently are not due to improvements in CRF (51).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 99%